A New Type of Lexicographic Product: Thesaurus of Text Strings. Field of EFL/ESL - Iosif Keselman (National Research University Higher School of Economics, 2016)
The "Thesaurus of Text Strings: The field of EFL/ESL" (TTS) is a structured collection of text fragments extracted from various texts, both printed and digital, that deal with teaching and learning English as a foreign or second language. While the sublanguage of ELF/ESL has been vastly discussed in literature, the TTS is a radically new type of dictionary due to the nature of its constituent objects, the text strings. A text string (TS) is a lexicographic object of unique status; as such, it has not been used before. It is different from all other objects traditionally treated in dictionaries of various types, such as words, collocations, idioms, proverbs and other reproducible linguistic units. TSs have been extracted from specialized texts, they are supposed to reflect the various aspects, even the minute ones, of the referential situations presented in the texts. The TSs in the Thesaurus are arranged mostly according to the conceptual structure of the Foreign Languages Teaching Methodology (a deductive logical procedure, 'head - bottom'), but on the lower, more concrete, levels of analysis the TSs have to be grouped following the opposite logical direction, 'bottom - up' as the Teaching Methodology concepts prove to be too general to differentiate between finer meaning distinctions of numerous TSs. The TTS supplies a considerable amount of carefully structured professional information in language form. It is aimed primarily at teachers of English who are not native speakers of the language and who wish to make their professional communication in English more authentic. It can also be used in classroom activities with students who are preparing for teaching careers. Thus, a conclusion may be justified that the TTS has both the theoretical significance for lexicography and the practical value as a good professional teaching material. The TTS may also be meaningfully considered against the background of today's Corpus Linguistics. Though not a 'true' corpus per se, it has certain features that are essentially similar to those of contemporary linguistic corpora.